Autonomous learning strategies: critical and creative thinking in primary education - Varías, Inés (2022)
The objective was to design a model of autonomous learning strategies aimed at developing critical and creative thinking in primary school students of Educational Institution No. 11239 Las Dunas Lambayeque - Peru. The research was of a primary propositional type, in which 58 students participated, who were administered a test on the development of critical and creative thinking. The instruments were validated by experts who agreed with a reliability coefficient of 0.80. The results regarding the level of development of critical and creative thinking indicate that 60.3% of the total are at the average level for critical thinking, and 65.5% are also at the intermediate level concerning creative thinking, which allows determining that the students participating in the research need to develop higher-order skills in different situations to make decisions and solve problems of daily life.